The influence of age and captivity on cardiac structure and function in rhesus macaques - T. G. Dawkins; B. A. Curry; A. Drane; V. N. Rivas; Y. Ueda; J. A. Stern; D. Philips; J. Negron-Del Valle; Lauren Brent; James Higham; Angelina Ruiz-Lambides; Noah Snyder-Mackler; et al. (GeroScience, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

An update on fermented plant-based dairy alternatives: Advances towards consumer acceptability and modern diets - Jonata M. Ueda; Virginia Fernández-Ruiz; Patricia Morales; Anabela Ferreira; Sandrina A. Heleno; Márcio Carocho (Food Research International, 2025)

Impact of the drying process and incorporation of natural preservatives on the viability of lactic acid bacteria in yogurts - Jonata M. Ueda; Patricia Morales; Márcio Carocho; Sandrina A. Heleno (Phytochemistry Letters, 2025)

Road to extinction: Archival samples unveiled the process of inbreeding depression during artificial breeding in an almost extinct butterfly species - Naoyuki Nakahama; Tatsuro Konagaya; Shouhei Ueda; Norio Hirai; Masaya Yago; Yuki A. Yaida; Atushi Ushimaru; Yuji Isagi (Biological Conservation, 2024)

Shutters-Inspired metal ions coordination hydrogel Strain/Pressure sensor for joint behavior evaluation and flatfeet correction - Xiaoyu Guan; Yanxia Zhu; Bingyuan Zhang; Xuhui Sun; Mohammed A. Abosheasha; Chunwei Gong; Sai Zheng; Dongping Li; Qingxin Han; Meng An; Motoki Ueda; Yoshihiro Ito (Chemical Engineering Journal, 2024)

Detrital zircon U–Pb ages and geochemistry of Devonian–Carboniferous sandstones and volcanic rocks of the Hida Gaien belt, Southwest Japan: Provenance reveals a Gondwanan lineage for the early Paleozoic tectonic evolution of proto-Japan - Keisuke Suzuki; Toshiyuki Kurihara; Teruki Sato; Hayato Ueda; Toshiro Takahashi; Simon A. Wilde; M. Satish-Kumar (Gondwana Research, 2023)

Fermented food/beverage and health: current perspectives - Alessandra Durazzo; Marcio Carocho; Sandrina A. Heleno; Mariana C. Pedrosa; Jonata M. Ueda; Lillian Barros; Eliana B. Souto; Antonello Santini; Massimo Lucarini (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

New cadinene-sesquiterpene from Chromolaena laevigata (lam.) R. M. King & H. Rob (Asteraceae) aerial parts and biological activities - Josiane A. Monteiro de Oliveira; Darlon Irineu Bernardi; Rodolfo Bento Balbinot; Márcia Regina Pereira Cabral; Érica Benassi Zanqueta; Eliana H. Endo; Benedito Prado Dias Filho; Tania Ueda Nakamura; Mariana Cecchetto Figueiredo; Ana Lucia Tasca Gois Ruiz; Mary Ann Foglio; Marta Regina Barrotto do Carmo; et al. (Natural Product Research, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Correction to: Common findings of blaCTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2019)

Inherited cardiomyopathies in veterinary medicine - Joshua A. Stern; Yu Ueda (Pflügers Archiv - European Journal of Physiology, 2019)

Immunohistochemical Cross-Reactivity Between Paracoccidioides sp. from Dolphins and Histoplasma capsulatum - Godai Shumoto; Keiichi Ueda; Sayaka Yamaguchi; Takashi Kaneshima; Toshihiro Konno; Yoshie Terashima; Atsushi Yamamoto; Luciene A. Nagashima; Eiko N. Itano; Ayako Sano (Mycopathologia, 2018)

Batesian insect-insect mimicry-related explosive radiation of ancient alienopterid cockroaches - Peter Vršanský; Günter Bechly; Qingqing Zhang; Edmund A. Jarzembowski; Tomáš Mlynský; Lucia Šmídová; Peter Barna; Matúš Kúdela; Danil Aristov; Sonia Bigalk; Lars Krogmann; Liqin Li; et al. (Biologia, 2018)

Perovskite-type titanate zirconate as photocatalyst for textile wastewater treatment - A. M. Ferrari-Lima; A. C. Ueda; E. A. Bergamo; R. G. Marques; E. A. V. Ferri; C. S. Pinto; C. A. A. Pereira; P. H. Yassue-Cordeiro; R. P. Souza (Environmental Science and Pollution Research, 2017)

Common findings of bla CTX-M-55-encoding 104–139 kbp plasmids harbored by extended-spectrum β-lactamase-producing Escherichia coli in pork meat, wholesale market workers, and patients with urinary tract infection in Vietnam - T. A. V. Hoang; T. N. H. Nguyen; S. Ueda; Q. P. Le; T. T. N. Tran; T. N. D. Nguyen; T. V. K. Dao; M. T. Tran; T. T. T. Le; T. L. Le; T. Nakayama; I. Hirai; et al. (Current Microbiology, 2017)

Enhanced loading regimen of teicoplanin is necessary to achieve therapeutic pharmacokinetics levels for the improvement of clinical outcomes in patients with renal dysfunction - T. Ueda; Y. Takesue; K. Nakajima; K. Ichiki; A. Doita; Y. Wada; T. Tsuchida; Y. Takahashi; M. Ishihara; H. Ikeuchi; M. Uchino; T. Kimura (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Ecological differences in response of bird species to radioactivity from Chernobyl and Fukushima - A. P. Møller; T. A. Mousseau; I. Nishiumi; K. Ueda (Journal of Ornithology, 2015)

Effect of habitat transformation from grassland to Acacia mangium plantation on dung beetle assemblage in East Kalimantan, Indonesia - Akira Ueda; Dhian Dwibadra; Woro A. Noerdjito; Sugiarto; Masahiro Kon; Teruo Ochi; Masayoshi Takahashi; Kenji Fukuyama (Journal of Insect Conservation, 2015)

Exogenous ghrelin improves blood flow distribution in pulmonary hypertension—assessed using synchrotron radiation microangiography - Daryl O. Schwenke; Emily A. Gray; James T. Pearson; Takashi Sonobe; Hatsue Ishibashi-Ueda; Isabel Campillo; Kenji Kangawa; Keiji Umetani; Mikiyasu Shirai (Pflügers Archiv - European Journal of Physiology, 2011)

The orf virus inhibitor of apoptosis functions in a Bcl-2-like manner, binding and neutralizing a set of BH3-only proteins and active Bax - Dana Westphal; Elizabeth C. Ledgerwood; Joel D. A. Tyndall; Merilyn H. Hibma; Norihito Ueda; Stephen B. Fleming; Andrew A. Mercer (Apoptosis, 2009)

Virulence and antibiotic susceptibility of Aeromonas spp. isolated from drinking water - Denise de Oliveira Scoaris; Jean Colacite; Celso V. Nakamura; Tânia Ueda-Nakamura; Benício A. de Abreu Filho; Benedito P. Dias Filho (Antonie van Leeuwenhoek, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Bovine and water buffalo Mx2 genes: polymorphism and antiviral activity - H. A. E. Babiker; Y. Nakatsu; K. Yamada; A. Yoneda; A. Takada; J. Ueda; H. Hata; T. Watanabe (Immunogenetics, 2006)

Population Research of Genetic Polymorphism at Amino Acid Position 631 in Chicken Mx Protein with Differential Antiviral Activity - T. Seyama; J. H. Ko; M. Ohe; N. Sasaoka; A. Okada; H. Gomi; A. Yoneda; J. Ueda; M. Nishibori; S. Okamoto; Y. Maeda; T. Watanabe (Biochemical Genetics, 2006)

F-Box-Like Domains are Present in Most Poxvirus Ankyrin Repeat Proteins - Andrew A. Mercer; Stephen B. Fleming; Norihito Ueda (Virus Genes, 2005)

Effects of an Environmental Estrogen on Male Gulf Pipefish, Syngnathus scovelli (Evermann and Kendall), a Male Brooding Teleost - N. Ueda; C. Partridge; J. Bolland; J. Hemming; T. Sherman; A. Boettcher (Bulletin of Environmental Contamination and Toxicology, 2005)

Heme oxygenase-1 inhibits cigarette smoke-induced increase in the tracheal mucosal permeability in guinea pigs in vivo - A. Tagawa; T. Kaneko; T. Shinohara; A. Ueda; T. Sato; Y. Ishigatsubo (Inflammation Research, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Elimination of chrysanthemum stunt viroid from an infected chrysanthemum cultivar by shoot regeneration from a leaf primordium-free shoot apical meristem dome attached to a root tip - M. Hosokawa; A. Otake; K. Ohishi; E. Ueda; T. Hayashi; S. Yazawa (Plant Cell Reports, 2004)

Merging of multiple signals regulating Δ9 fatty acid desaturase gene transcription in Saccharomyces cerevisiae - Y. Nakagawa; A. Ueda; Y. Kaneko; S. Harashima (Molecular Genetics and Genomics, 2003)

Detection of Japanese yam mosaic virus by RT-LAMP - S. Fukuta; T. Iida; Y. Mizukami; A. Ishida; J. Ueda; M. Kanbe; Y. Ishimoto (Archives of Virology, 2003)

Analysis of salt-inducible genes in barley roots by differential display - A. Ueda; W. Shi; T. Nakamura; T. Takabe (Journal of Plant Research, 2002)

Renal damage and salt-dependent hypertension in aged transgenic mice overexpressing endothelin-1 - T. Shindo; H. Kurihara; K. Maemura; Y. Kurihara; O. Ueda; H. Suzuki; T. Kuwaki; K.-H. Ju; Y. Wang; A. Ebihara; H. Nishimatsu; N. Moriyama; et al. (Journal of Molecular Medicine, 2002)

Nephrotoxicity of D -propargylglycine in mice - R. Konno; M. Ikeda; K. Yamaguchi; Y. Ueda; A. Niwa (Archives of Toxicology, 2000)

Polychlorinated Dibenzo- p -Dioxins (PCDDs), Dibenzofurans (PCDFs), Biphenyls (PCBs), and Organochlorine Pesticides in Yellow-Blotched Map Turtle from the Pascagoula River Basin, Mississippi, USA - K. Kannan; M. Ueda; J. A. Shelby; M. T. Mendonca; M. Kawano; M. Matsuda; T. Wakimoto; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 2000)

Human cytotoxic T-lymphocyte responses specific for peptides of the wild-type Wilms' tumor gene ( WT1 ) product - Y. Oka; O. A. Elisseeva; A. Tsuboi; H. Ogawa; H. Tamaki; H. Li; Y. Oji; E. H. Kim; T. Soma; M. Asada; K. Ueda; E. Maruya; et al. (Immunogenetics, 2000)

Expression of the SNF1 gene from Candida tropicalis is required for growth on various carbon sources, including glucose - Tamotsu Kanai; Kouji Ogawa; Mitsuyoshi Ueda; A. Tanaka (Archives of Microbiology, 1999)

Hydrothermal carbonates in altered wall rocks at the Uwamuki Kuroko deposits, Japan - N. Shikazono; M. Hoshino; M. Utada; M. Nakata; A. Ueda (Mineralium Deposita, 1998)

Immunochemically distinct NADP-linked isocitrate dehydrogenase isozymes in mitochondria and peroxisomes of Candida tropicalis - Toshiya Imajo; Hiroyuki Kawachi; Haruyuki Atomi; Shin-ichi Sanuki; Setsuko Yamamoto; Mitsuyoshi Ueda; A. Tanaka (Archives of Microbiology, 1997)

Protein kinase C-independent correlation between P-glycoprotein expression and volume sensitivity of Cl− channel - A. Miwa; K. Ueda; Y. Okada (The Journal of Membrane Biology, 1997)

The upstream region of the isocitrate lyase gene (UPR-ICL) of Candida tropicalis induces gene expression in both Saccharomyces cerevisiae and Escherichia coli by acetate via two distinct promoters - Haruyuki Atomi; K. Umemura; Takanori Higashijima; Tamotsu Kanai; Yoshihisa Yotsumoto; Yutaka Teranishi; Mitsuyoshi Ueda; A. Tanaka (Archives of Microbiology, 1995)

Novel NADP-linked isocitrate dehydrogenase present in peroxisomes of n-alkane-utilizing yeast, Candida tropicalis: comparison with mitochondrial NAD-linked isocitrate dehydrogenase - Setsuko Yamamoto; Haruyuki Atomi; Mitsuyoshi Ueda; A. Tanaka (Archives of Microbiology, 1995)

Provocation of respiratory allergy in guinea pigs following inhalation of free toluene diisocyanate - K. Aoyama; J. Huang; A. Ueda; T. Matsushita (Archives of Environmental Contamination and Toxicology, 1994)

Rapid detection of African horsesickness virus by the reverse transcriptase polymerase chain reaction (RT-PCR) using the amplimer for segment 3 (VP3 gene) - K. Sakamoto; R. Punyahotra; N. Mizukoshi; S. Ueda; H. Imagawa; T. Sugiura; M. Kamada; A. Fukusho (Archives of Virology, 1994)

A new typing method for the avian infectious bronchitis virus using polymerase chain reaction and restriction enzyme fragment length polymorphism - Z. Lin; A. Kato; Y. Kudou; S. Ueda (Archives of Virology, 1991)

Typing of recent infectious bronchitis virus isolates causing nephritis in chicken - Z. Lin; A. Kato; Y. Kudou; K. Umeda; S. Ueda (Archives of Virology, 1991)

Generation and characterization of the human immunodeficiency virus type 1 mutants - A. Adachi; N. Ono; H. Sakai; K. Ogawa; R. Shibata; T. Kiyomasu; H. Masuike; S. Ueda (Archives of Virology, 1991)

Characterization of a temperature-sensitive mutant in the RNA polymerase PB2 subunit gene of influenza A/WSN/33 virus - K. Yamanaka; N. Ogasawara; M. Ueda; H. Yoshikawa; A. Ishihama; K. Nagata (Archives of Virology, 1990)

The effect of actinomycin D on the synthesis of influenza virus-specific RNA - A. Sugiura; M. Ueda; C. Enomoto (Archives of Virology, 1969)